Managing geothermal project implementation conflicts through mediation: A case of Olkaria IV Project, Nakuru county, Kenya (Journal of Sustainability, Environment and Peace, 2022)
Geothermal energy installations generate conflicts that escalate when improperly managed. Studies from outside Kenya have demonstrated application of mediation in managing conflicts over natural resources. However, its efficacy has not been adequately covered in Kenya. This study used the case of mediation between project affected persons (PAPs) and the developers of Olkaria IV energy project to document the process, to assess its role in resolving conflicts that emanated from the implementation of the project. A PAPs’ household heads survey, focus group discussions (FGDs), and key informant interviews (KII) were conducted. Primary data was collected on pre-mediation preparations; mediation attributes, post-mediation buy-in and endorsements and the sequel of mediation. Secondary data was obtained from documents available in the mediation archive. The protagonists, that is, the Kenya Electricity Generating Company (KenGen) and PAPs agreed to use mediation to resolve their conflicts. The mediation neutralized conflicts between KenGen and the PAPs, mended relationships between them, improved PAPs’ livelihoods and smoothened project operations. The community representatives, selected by themselves, regularly reported back and held consultation with the larger community. This promoted acceptability of the results and is here presented as a good practice, in addition to having competent mediators with good listening and probing skills. Further, inclusion of women and youth in the mediation exercise combined with freedom of expression during the mediation clinics, ensured that the weaker gender’s voice was heard and its input incorporated in the agreement. In spite of the above, there is a need for greater democratization for the PAPs representation, and a more comprehensive documentation of the process. The last two provide opportunity for copying this case for an improved mediation process. Finally, it is recommended that policies be formulated to provide for use of mediations as an alternative dispute resolution mechanism, in future project developmental conflicts in Kenya.
Keywords: conflicts; geothermal; mediation; project affected persons; relocation; sustainability